Disordered minerals and disease of soft tissue and bones in chronic kidney disease - Swanepoel, Charles R (African Journal of Nephrology, 2023)
This article briefly reviews the mineral and bone disorder (MBD) found in patients with chronic kidney disease (CKD) and should provide a useful summary for trainees in nephrology and internal medicine. The storage of minerals is one of the principal roles of our bones, which are alive and are constantly being remodelled under the influence of vitamin D and parathyroid hormone (PTH), aided and abetted by calcium and phosphates. This occurs in a controlled fashion in healthy individuals. In patients with CKD, this control is lost and either an exaggerated, ineffectual remodelling takes place, resulting in the removal (in the case of high-turnover bone disease) or inadequate (in low-turnover bone disease) deposition of minerals. Vascular (and other soft tissue) calcification accompanies MBD, with phosphate and calcium playing major roles in the pathogenesis of the condition. The development of MBD is insidious and evident by changes in blood PTH, calcium and phosphate levels seen as early as stage 3 CKD. Vascular calcification may also be observed at this early stage. Various reports have demonstrated associations between these abnormal blood levels and morbidity and mortality; however, randomised controlled studies are lacking that show definite proof of cause and effect. In resource-limited countries, the control of PTH is restricted to the use of basic, inexpensive medicines, and patients with CKD can have inadequate means to afford blood tests. The use of vitamin D must be balanced between the use of natural vitamin D (a relatively cheap option) and active vitamin D. The cost of intravenous vitamin D analogues can be prohibitive. The more expensive phosphate binders (mostly non-calcium containing) too are unaffordable for most African patients. The surgical expertise to perform parathyroidectomies is limited to only certain major centres throughout the continent.